Detection and Characterization of Unintended RF Emissions on Wideband Real Data - Sathyanarayanan, Venkatesh; Gerstoft, Peter (International Conference on Signal Processing and Communications, 2024)
Sensing and understanding all signals in an RF-secure military or civilian setup is important, this includes unin-tended RF emissions called emanations. Prior work in detecting emanations involves profiling, which is hardware (HW) specific and hence not a scalable approach. Our technique looks for a generic signature of harmonics in the frequency domain without knowledge of HW. It detects emanation and characterizes it by estimating the pitch frequency of harmonic. A signal model for emanations, HW, and channel effects is provided. A mathematical treatment showcases the removal of artifacts and extracts the harmonic structure. The performance is showcased on In-phase and Quadrature-phase (IQ) data collected using a Signal Hound software-defined radio (SDR) in a shielded room. Data is collected from 0.1-1.1 GHz and 100 ms duration. Emanations are detected for a laptop, and a desktop connected to a monitor. The unique contribution of this work is the detection of emanation without HW knowledge, with mathematical justification and demonstrated performance on wideband real data.